Martin Luther's Basic Theological Writings : - Luther, Martin, 1483-1546 (Book collections on Project MUSE., 2012)
"Martin Luther's Basic Theological Writings, a single-volume introduction to Luther's most influential, noted, and important writings in the modern translations-including excerpts of his sermons and letters-presents Luther the theologian 'steeped in the word of God, speaking to the whole church, ' even as it takes the reader straight to Luther the man, to his controversial Reformation insights, to his strongest convictions about God and Scripture and the life of the church, and most importantly to his theology-a still-exciting encounter with the meaning of Jesus Christ for each age. The third edition includes revised introductions, updated bibliography, index, and the addition of 'A Meditation on Christ's Passion' (1519), 'Treatise on the Blessed Sacrament' (1519), 'Sermon on the Sacrament of the Body and Blood of Christ#Against the Fanatics' (1526), 'Sermon in Castle Pleissenburg' (1539), and 'Consolation to Women Whose Pregnancies Have Not Gone Well' (1542), as well as new translations of 'A Practical Way to Pray' (1535) and 'On the Freedom of a Christian' (1520)"--Publisher description.